Post-common-envelope binary central stars of Planetary Nebulae in the OGLE-IV survey - Hlabathe, Michael (Department of Astronomy, 2016)
Planetary Nebulae (PNe) are defined as the ionized shells of circumstellar gas ejected through an intense stellar wind at the end of the star's life. PNe come in different shapes, from spherical to highly complex, non-spherical shapes. Mass loss in AGB stars is presumed as the shaping mechanism but how it results in different PNe morphologies is still unclear. Binary central stars that have undergone common envelope evolution are thought to be a possible solution to this longstanding problem. Using photometry from the OGLEIV survey, we present the newly identified close binary central stars of Planetary Nebulae (CSPNe), six in total. Of the six PNe with close binary CSPNe, one looks spherical which presents a very interesting argument in terms of our understanding of PNe evolution. The orbital distribution is derived and compared against current orbital distribution for binary CSPNe, with most binaries from the distribution exhibiting orbital periods less than a day. A binary fraction estimate of 6% is presented and possible cases are discussed that might have influenced our estimation to be different from the expected 10-15%.